Diversifying selection detected in only a minority of xenobiotic-metabolizing CYP1-3 genes among primate species. (1st December 2020) - Chaney, Morgan E.; Romine, Melia G.; Piontkivska, Helen; Tosi, Anthony J.
Abstract: 1. Primates exhibit a high degree of among-species dietary diversity, which likely exposes them to varying levels of xenobiotic compounds. Here, we examined the evolution of primate CYP1-3 gene families, and we classified the 15 CYP1-3 gene subfamilies as either xenobiotic-metabolizing (XM) or endogenous-metabolizing (EM) based on sources in the P450 literature. 2. We predicted that XM P450s would show (1) greater variability in gene-copy number and (2) more evidence of diversifying selection and, especially on codons that encode the substrate-recognition sites (SRSs) for the final enzymes. 3. Counter to our first prediction, EM and XM P450s showed similar levels of variation in gene-copy number. We did find, however, that four XM P450 subfamilies ( CYP2C, CYP2D, CYP2E, and CYP3A ) showed evidence of diversifying selection while no EM subfamilies demonstrated any consistent signal of diversifying selection. Of these four, CYP2C, CYP2D, and CYP3A showed significant links between SRSs and diversifying selection. 4. These results reveal an amount of evolutionary dynamism that would not be expected when viewing P450 subfamilies along a simple binary EM/XM spectrum. We recommend that comparative studies of cytochrome P450 evolution should focus on the CYP2C, CYP2D, CYP2E, and CYP3A subfamilies.